A Comparative Study between Managed Aquifer Recharge and Other Community Water Supply Options in Coastal Bangladesh - Nawrin, Nazia; Sultana, Sarmin; Ahmed, Kazi Matin (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
The acute scarcity of safe water exists in disaster-prone coastal Bangladesh due to the occurrences of brackish or saline and arsenic contaminated groundwater, the salinization of freshwater ponds by inundation during storm surges, and brackish water aquaculture. Millions of people living there mainly depend on pond water and rainwater harvesting system and face severe difficulties to collect freshwater, particularly during the dry season. Therefore, various community water supply technologies, e.g., RO, SIDKO, RPWS, SkyHydrants etc. have been established to meet their daily needs, though the majority of these technologies fall short of the value of time and effort of water collection and sometimes fail to supply water of desired quality. Managed Aquifer Recharge (MAR) technique, also a community water supply system, was designed to provide safe water by creating underground storage of freshwater where ambient groundwater salinity is reduced by infiltrating rooftop or pond water through wells. Understanding the need to sort out the best water supply option, a comparative study has been conducted between MAR and other water supply technologies, and among all of them the MAR has been demonstrated as a low cost, reliable, sustainable, and durable option for providing safe drinking water to the community round the year. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 157-166